Melatonin production influenced by low frequency magnetic fields - Mohammed Ali, Esmail Abdo (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In several residential and occupational studies, suppression of nocturnal melatonin in humans, which is induced by magnetic field, has been reported. The pineal gland produces melatonin and consider it as its major secretory product, which has a vital role in human well-being and health as it was suggested by the growing literature. Generally, exposure to the electric field has many biological effects, and the research on which has recently made this neurohormone, which is associated with the generation and classification of electric field, a focal point. To raise the risk of cancer through changing the pineal glands’ regular functions and disrupting the melatonin’s nocturnal increase in its release and synthesis, exposure to magnetic fields has been hypothesized. It is very essential to ascertain whether hormonal levers are changed during the exposure of humans to a magnetic field at night because the evidence for the "melatonin hypothesis" relies chiefly upon rodent data. The field-induced alterations were failed to be observed by all studies which have investigated the alterations in melatonin under controlled laboratory conditions when humans are exposed to a magnetic field. However, melatonin levels are altered through the exposure to low frequency magnetic fields, as it has been proposed by several observational studies in occupational and residential settings, which usually differ in terms of the presence of possible confounders, the individuals’ health status and their general characteristics, the exposure conditions, and the attained measurement’s precisions, durations and types. The associated differences in the duration of exposure may lead to this model of conflicting results. In the laboratory studies, only one night of exposure to a magnetic field was received by volunteers. In contrast, participants in the observational studies, usually for long periods on a daily basis, received chronic exposures to such fields. The consistent measurements of each melatonin over time is considered as another related possible explanation. It is unknown if the frequent magnetic field exposures suppress the inherent stability of each measurement of melatonin over time. In conclusion, the explanation of the contrasting results obtained in laboratory studies, and not in observational ones, could be helped by the evidence for improved suppression or increased variable measurements of melatonin attained in studies with longer controlled exposures.